RESEARCH HOTSPOTS AND TRENDS IN MATHEMATICS PEDAGOGICAL CONTENT KNOWLEDGE FROM A CITESPACE PERSPECTIVE：AN ANALYSIS OF SSCI LITERATURE OVER THE PAST DECADE - Liu, Yang; Kamarudin, Nurzatulshima; Sulaiman, Tajularipin (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
In order to grasp the research results of mathematics pedagogical content knowledge(MPCK), this article adopts bibliometric methods and uses CiteSpace software to visually analyze the research literature on MPCK in the past decade, and sort out the research hotspots and future trends of MPCK. The results show that scholars’ research on MPCK can be roughly divided into four areas: technology-enabled integration of MPCK, teacher knowledge construction and professional development, integration of disciplinary nature and cognitive processes, and scaled-up practice and innovation in assessment systems.Based on the analysis results, inspirations for promoting mathematics teachers to improve their subject teaching knowledge are proposed: firstly, build a school climate of trust; secondly, establish coherent digital technology systems; thirdly, strengthen continuity in teacher training, aiming to contribute certain reference value to subsequent research.